Discovery of a Novel Polyomavirus in Acute Diarrheal Samples from Children - Ramqvist, Torbjörn; Yu, Guixia; Greninger, Alexander L.; Isa, Pavel; Phan, Tung G.; Martínez, Miguel Angel; De la Luz Sanchez, Maria; Contreras, Juan Francisco; Santos Preciado, José Ignacio; Parsonnet, Julie; Miller, Steve; DeRisi, Joseph L.; et al. (Public Library of Science, 2012)
Polyomaviruses are small circular DNA viruses associated with chronic infections and tumors in both human and animal hosts. Using an unbiased deep sequencing approach, we identified a novel, highly divergent polyomavirus, provisionally named MX polyomavirus (MXPyV), in stool samples from children. The ,5.0 kB viral genome exhibits little overall homology (,46% amino acid identity) to known polyomaviruses, and, due to phylogenetic variation among its individual proteins, cannot be placed in any existing taxonomic group. PCR-based screening detected MXPyV in 28 of 834 (3.4%) fecal samples collected from California, Mexico, and Chile, and 1 of 136 (0.74%) of respiratory samples from Mexico, but not in blood or urine samples from immunocompromised patients. By quantitative PCR, the measured titers of MXPyV in human stool at 10% (weight/volume) were as high as 15,075 copies. No association was found between the presence of MXPyV and diarrhea, although girls were more likely to shed MXPyV in the stool than boys (p = 0.012). In one child, viral shedding was observed in two stools obtained 91 days apart, raising the possibility of chronic infection by MXPyV. A multiple sequence alignment revealed that MXPyV is a closely related variant of the recently reported MWPyV and HPyV10 polyomaviruses. Further studies will be important to determine the association, if any, of MXPyV with disease in humans.